A Retrospective review of computer tomography (CT) use by an academic emergency department - Swartzberg, Kylen Mark (My University, 2018)
Study Objective There is growing pressure to reduce unnecessary CT scan imaging requests from the Emergency Department (ED), however acceptable usage rates and diagnostic yields remain scanty. The aim of this study was to describe indications, clinical categories and positive yield rates of patients receiving CT scans in the ED. Methods A retrospective record review of all patients who received CT scans at an urban adult academic ED, over a four month period. Primary outcomes were to establish CT scan usage and positive yield rates. Other outcomes included analysis of indications, demographics and anatomical areas scanned. Results There were 1 010 scans analysed. The median age of patients was 36 years (4 to 93 years). Males received 64.3% of all scans as well as 75.7% of the scans performed for trauma. The majority of the scans were for trauma patients but non-trauma patients had a higher positive yield which was 61.8% compared to traumatic positivity yields 47.1% (p-value <0.001). The majority of scans performed were of the head (58%) and neck (20%) with lowest positivity yields rates of 48.9% and 17% respectively. The overall usage rate was 4.6% and overall positivity rate 53.8%. Conclusions A negative CT scan does not necessarily mean that the test was not indicated. Higher positivity yield rates may, in fact, reflect insufficient use of CT scanning from the ED. Local guidelines should be established to ensure judicious and effective clinical use of CT scans. Published as: Swartzberg K, Goldstein L N, High positive computed tomography yields in the emergency department might not be a positive finding. South African Medical Journal 2018;108(3):230-234. DOI:10.7196/SAMJ.2018.v108i3.12635
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine (Emergency Medicine). Johannesburg, 2018
Keywords: A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine (Emergency Medicine).